Meta Analysis the Relationship of Social Support on Depression in Pregnant Women - Mitha Amelia Rahmawati; Muthia Syafira (Journal of Epidemiology and Public Health, 2021)
Background: Depression in pregnancy can lead to poor pregnancy outcomes, such as pre-eclampsia, insufficient weight gain, and preterm delivery which can progress to postpartum depression thereby posing a risk to the mother-infant bond and impacting the child's social development at a further level. Social support is one of the important factors that can increase the risk of depression during pregnancy, because with a lack of social support, the increased risk of depression in pregnant or postpartum women will enhance. The purpose of this study was to estimate the relationship between low social support and depression in pregnancy.